Le rôle du français parlé dans Histoire vécue d'Artaud-Mômo d'Antonin Artaud - Schneller, Dóra (Verbum – Analecta Neolatina, 2006)
Histoire vécue d'Artaud-Mômo is the 26th volume, the last so far, of Antonin Artaud's complete works. It was first published in 1994 and it consists of the texts that Artaud composed for a conference in the Vieux-Colombier theatre, Paris in 1947. As its title suggests, Histoire vécue d'Artaud-Mômo is an autobiographical work in which Artaud recalls and tells themost important events of his life, emphasing the story of his hospitalisation. The text is characterized by the use of spoken French. By introducing a theatre and oral style, Artaud wanted to make the ambiance of the performance more intimate, he tried to overcome the distance between the stage and the auditorium. But first and foremost he wanted to live once more his life, to become an actor and director of the Theatre of Cruelty. We can discover several common aspects between Artaud's text and Voyage au bout de la nuit by Céline. Some of the points they share are the importance of voyage narratives, autobiographical elements, the use of spoken and popular French as well as argot, the revolt against institutions established by society, the feeling of the tragic, a pessimistic vision of the world, and finally the theme of death which is omnipresent in Artaud's and Céline's works.